PERFORMA REPRODUKSI IKAN BETOK (Anabas testudineus) BETINA DENGAN PEMBERIAN PAKAN BUATAN BERBAHAN BAKU TEPUNG KEONG MAS (Pomacea canaliculata) - ma’ruf, muhammad masrur (Jurnal Perikanan Unram, 2019)
Abstract: Climbing perch (Anabas testudineus) is one of the potential local fish species to be cultivated. The purpose of this study was to learn and evaluate the effect of feeding made from golden snail (Pomacea canaliculata) on the level of gonad maturity. The study was conducted in July - August 2018. The climbing perch (A. testudineus) originated from natural catchments in the rice fields of Rias village, Toboali Subdistrict, South Bangka Regency. The used fish are 150 fish with a weight of 2 ± 10 grams. The treatment given by artificial feed made from golden snail (P. canaliculata) with protein content in feed was 32%, 34%, 36%, 38% and control using commercial feed with a protein content of 31 - 33%. The results showed the value of the Gonad Maturity Index (IKG) with gonad weight at the start of the study at 0.5 gram. After treatment with artificial feed made from golden snail (P. canaliculata) flour, the results of statistical tests showed that the control was significantly different from the treatment in the GSI observation with a range of values ??of 16% ± 0.02 in treatment P.38%, HSI with a value of 8% ± 0.01 in treatment P.38%. Fecundity of climbing perch (A. testudineus) obtained in the results of the study with a range of 509 ± 4,686 items. The development of the initial gonad maturity (TKG) of the study (TKG II) after being given artificial feed made from golden snails (P. canaliculata) increased with the level of gonad maturity reaching stage IV. Keywords: Anabas testudineus, Pomacea canaliculata, gonad maturity, IKG, fecundity, TKG.